Clinical efficacy of middle pancreatectomy contrasts distal pancreatectomy: a single‐institution experience and review of literature. Issue 5 (21st March 2019) - Tan, Zhen; Chen, Peng; Dong, Zheng; Zhou, Bin; Guo, Wei Dong
Abstract : Background: We aim to analyse the difference of clinical efficacy between middle pancreatectomy (MP) and distal pancreatectomy (DP). Methods: A retrospective study was used to analyse 39 cases of MP and 52 cases of DP from the Department of Hepatopancreatobiliary Surgery of the Affiliated Hospital of Qingdao University from February 2007 to December 2016. Furthermore, we identify randomized controlled trials or strictly designed clinical controlled trials on MP and DP. We performed a meta‐analysis of the final included studies using RevMan 5.3 software to illustrate the differences in efficacy between MP and DP. Results: In the MP group, the operation time and diet start time were significantly longer than DP group. However, there was no significant difference in serious complications including clinically significant pancreatic fistula (grades B and C), delayed gastric emptying, reoperative and mortality. Furthermore, compared with DP, patients in MP group could benefit from long‐term post‐operative exocrine and endocrine function. Finally, we performed a meta‐analysis including 14 studies with a total of 1104 patients and proved that the pancreatic fistula rate, endocrine and exocrine function were significantly different in the two groups. Conclusion: The MP is a safe and feasible surgical method. It can well preserve the endocrine and exocrine function of pancreas and improve the life quality of patients. Abstract : The middle pancreatectomy is a safe and feasible surgical method. It can well preserve the endocrine and exocrinosity function of pancreas and improve the quality of patient's life.